Rural primary school ESL teachers' code switching practices in the Padawan district of Sarawak / Flowrese William Abong - William Abong, Flowrese (2012)
This study aims to find out the purpose, extent and why ESL teachers code switch in the predominant Bidayuh populated primary schools in the Padawan district in Sarawak. Thirty primary schools participated in the study. Data were collected using questionnaire and interview techniques. Three sets of questionnaire were distributed to each of these schools and a total of 84 ESL teachers had returned the completed forms; a return rate of 85.7%. Data were analysed using descriptive and inferential statistics. The findings revealed that ESL teachers code switch in the classroom for various purposes and at varying degrees. However, despite the fact that the majority of the pupils and teachers in these schools are Bidayuh, the findings revealed that the teachers hardly code switch to the Bidayuh dialect which is the pupils 'first language, instead they code switch to Bahasa Malaysia, the other formal language that the pupils learned in school. On the teachers' perception for the reasons for code switching, the result supported previous studies on the various functions for code switching in the classroom domain. Based on the findings, this study recommends that code switching be allowed in the ESL classroom for the purpose of facilitating the teaching and learning process especially in schools in the rural areas. It also hopes to contribute to future research in the field.